Readings in the social control of industry : selected by a committee of The American Economic Association - American Economic Association; Hoover, Edgar Malone; Dean, Joel (Philadelphia: The Blakiston Company, 1942)
This book examines monopoly and competition with reference to the US. Topics discussed include: monopoly in law and economics, unfair competition, Antitrust laws among others.
"Selection committee... Edgar M. Hoover, jr., Joel Dean."
Includes bibliographical references and index.
lje 16/06/2017
Loans
Keywords: Industrial policy; Trusts, Industrial; Competition, Unfair